‘The Social factors associated with student violence against teachers and administrators: A field study on high schools eastern sector of Ahsaa - Al-Barih, Abdul Hadi Ahmed (Journal of Humanities & Social Sciences, 2018)
The current study tries determining social factors associated with student violence against teachers and administrators the Secondary schools of eastern sector at Ahsa. It targeted to identify the nature of student violence against teachers and administrators, that to identify the student's motivation to make practice violence against a teacher or administrative, and learn about the social factors that lead to student violence against teachers and administrators.This study is the descriptive, through using social survey methodology intentional sample Statistics practitioners student violence against teachers and administrators at public school became the size of the sample (144) of (3350), as well as a simple intentional sample of teachers and administrators managers, agents and counselors and administrative assistants, at government School itself to become the size of the sample (58) teacher, three (3) directors, (3) three students guiders, and (3) of assistant staff from (290) teacher, (14) and director (14) guider and (15) a student counselor.This study found a set of results that tried to answer the questions of the study. the results were (47%) of violence against the teachers is orally, (22%) symbolic , (48%) inside the classroom ,(38%) in the end of school day. the study put forward numbers of recommendations that can be guided by experts and specialists, and decision- makers on the subject of the current.
Keywords: social factors; student violence; teachers and administrators; Al-Ahsa region